2021
DOI: 10.1073/pnas.2107830118
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study reveals genetic variants associated with HIV-1C infection in a Botswana study population

Abstract: Although there have been many studies of gene variant association with different stages of HIV/AIDS progression in United States and European cohorts, few gene-association studies have assessed genic determinants in sub-Saharan African populations, which have the highest density of HIV infections worldwide. We carried out genome-wide association studies on 766 study participants at risk for HIV-1 subtype C (HIV-1C) infection in Botswana. Three gene associations (AP3B1, PTPRA, and NEO1) were shown to have signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Nonetheless, the study has some limitations. However, it should be noted that our focus is on deleterious variants and variation among HIV-1 positive and negative individuals and not on the genetic susceptibility or association studies of HIV-1 in Botswana as previously reported ( Xie et al, 2017 ; Shevchenko et al, 2021 ). Also, the sample size is relatively modest and larger sample sizes would probably yield more findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the study has some limitations. However, it should be noted that our focus is on deleterious variants and variation among HIV-1 positive and negative individuals and not on the genetic susceptibility or association studies of HIV-1 in Botswana as previously reported ( Xie et al, 2017 ; Shevchenko et al, 2021 ). Also, the sample size is relatively modest and larger sample sizes would probably yield more findings.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we reported a WGS study as part of ongoing and recent study ( Shevchenko et al, 2021 ) on clinical phenotypes of HIV-1 in Africa. Notably, we generated a catalogue of candidate modifier genes and their associated pathways that clustered in pathophysiological pathways important in HIV-1 and with implications for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one should keep an open eye for a connection of PTPRA variants with other pathologies as well. As an example we mention its recently suggested ties with HIV-1C acquisition and pathogenesis ( Shevchenko et al, 2021 ), although the small size of the studied cohort implies the need for follow-up studies on PTPRA as a determinant in viral transmitted diseases.…”
Section: Documented Genetic Variabilitymentioning
confidence: 99%